SISTEM AKUNTANSI PERSEDIAN SYARIAH - Hafifah Munawarah Siahaan; Wila Triana; Yasha Arsani (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2024)
Inventory is a crucial asset in business operations as it directly influences production continuity, cost of goods sold, and the accuracy of financial reporting. Effective inventory management requires an accounting information system (AIS) capable of recording, controlling, and reporting inventory transactions reliably. This article discusses two primary inventory recording methods—the perpetual inventory method and the physical (periodic) inventory method—along with their characteristics, advantages, and application within companies. Furthermore, the article explains the detailed procedures that form the inventory accounting system, including recording finished goods, cost of goods sold, sales returns, purchases, warehouse requests and issuances, and the physical inventory counting system. Internal control elements are also highlighted as essential components to ensure the reliability of inventory data through proper segregation of duties, document authorization, and sound practices in recording and physical verification. Overall, a well-structured inventory accounting system supported by strong internal controls enhances data accuracy, prevents fraud, and supports managerial decision-making. Keywords: inventory, accounting information system, inventory recording methods, internal control, accounting procedures.